A sex-specific role for the bed nucleus of the stria terminalis in proactive defensive behavior - Guerra, Diana P.; Wang, Wei; Souza, Karienn A.; Moscarello, Justin M. (Neuropsychopharmacology (New York, N.Y.), 2023)
The bed nucleus of the stria terminalis (BNST) is a forebrain region implicated in aversive responses to uncertain threat. Much of the work on the role of BNST in defensive behavior has used Pavlovian paradigms in which the subject reacts to aversive stimuli delivered in a pattern determined entirely by the experimenter. Here, we explore the contribution of BNST to a task in which subjects learn a proactive response that prevents the delivery of an aversive outcome. To this end, male and female rats were trained to shuttle during a tone to avoid shock in a standard two-way signaled active avoidance paradigm. Chemogenetic inhibition (hM4Di) of BNST attenuated the expression of the avoidance response in male but not female rats. Inactivation of the neighboring medial septum in males produced no effect on avoidance, demonstrating that our effect was specific to BNST. A follow up study comparing hM4Di inhibition to hM3Dq activation of BNST in males replicated the effect of inhibition and demonstrated that activation of BNST extended the period of tone-evoked shuttling. These data support the novel conclusion that BNST mediates two-way avoidance behavior in male rats and suggest the intriguing possibility that the systems underlying proactive defensive behavior are sex-specific.